HUBUNGAN KOORDINASI MATA TANGAN DAN KESEIMBANGAN TERHADAP KEMAMPUAN PASSSING ATAS BOLA VOLI SISWA MI NURUL IMAM BULU KECAMATAN AWANGPONE KABUPATEN BONE - Darmawati R; Khalid Rijaluddin; Maria Herlinda Dos Santos; Sirwanti, Sirwanti (Bajang Institute, 2025)
This study analyses the relationship between eye-hand coordination and balance on volleyball top Passing ability in MI Nurul Imam Bulu students in Awangpone District, Bone Regency. This study uses quantitative methods with a correlational approach. The research sample was 25 students selected based on convenience sampling technique. Data were collected through eye-hand coordination tests, balance tests, and upper Passing ability tests, then analyzed using SPSS statistical tests to determine the correlation between the research variables. The results showed a significant contribution of hand-eye coordination to the upper Passing ability (sig. <0.05) and the contribution of balance to the upper Passing ability. Eye-hand coordination and balance contributed 30% to volleyball top Passing ability, with the rest influenced by other factors. The conclusion of this study emphasizes the importance of developing eye-hand coordination and balance in volleyball training to improve students' upper Passing skills.